PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAAN PELANGGAN DI YASMIN SALON BANGKINANG KOTA - Henrizal Henrizal; Mustafa Kamal; Litra Diantara; Adi Setiawan; Maulina Agustiningsih (Komunitas Manajemen Kompetitif, 2025)
The purpose of this study is to examine how customer satisfaction at Yasmin Salon in Bangkinang City is impacted by service quality. Customers of Yasmin Salon are given questionnaires as part of this study's quantitative survey strategy, which collects data. 97 individuals were randomly selected to participate in this study as respondents. Simple linear regression analysis was used to examine the gathered data. The findings of the study demonstrate that customer happiness is significantly impacted by service quality.Aspects of service quality such as reliability, responsiveness, certainty, empathy, and physical evidence all contribute positively to customer satisfaction. The conclusion of this research is that improving the quality of service at Yasmin Salon can increase the level of customer satisfaction, which in turn can increase customer loyalty and trust in the services provided by the salon.